Biallelic mutations in the TOGARAM1 gene cause a novel primary ciliopathy. Issue 8 (3rd August 2020) - Morbidoni, Valeria; Agolini, Emanuele; Slep, Kevin C; Pannone, Luca; Zuccarello, Daniela; Cassina, Matteo; Grosso, Enrico; Gai, Giorgia; Salviati, Leonardo; Dallapiccola, Bruno; Novelli, Antonio; Martinelli, Simone; et al.
Abstract : Background: Dysfunction in non-motile cilia is associated with a broad spectrum of developmental disorders characterised by clinical heterogeneity. While over 100 genes have been associated with primary ciliopathies, with wide phenotypic overlap, some patients still lack a molecular diagnosis. Objective: To investigate and functionally characterise the molecular cause of a malformation disorder observed in two sibling fetuses characterised by microphthalmia, cleft lip and palate, and brain anomalies. Methods: A trio-based whole exome sequencing (WES) strategy was used to identify candidate variants in the TOGARAM1 gene. In silico, in vitro and in vivo ( Caenorhabditis elegans ) studies were carried out to explore the impact of mutations on protein structure and function, and relevant biological processes. Results: TOGARAM1 encodes a member of the Crescerin1 family of proteins regulating microtubule dynamics. Its orthologue in C. elegans, che-12, is expressed in a subset of sensory neurons and localises in the dendritic cilium where it is required for chemosensation. Nematode lines harbouring the corresponding missense variant in TOGARAM1 were generated by CRISPR/Cas9 technology. Although chemotaxis ability on a NaCl gradient was not affected, che-12 point mutants displayed impaired lipophilic dye uptake, with shorter and altered cilia in sensory neurons. Finally, in vitro analysis of microtubule polymerisation in the presence of wild-type or mutant TOG2 domain revealed a faster polymerisation associated with the mutant protein, suggesting aberrant tubulin binding. Conclusions: Our data are in favour of a causative role of TOGARAM1 variants in the pathogenesis of this novel disorder, connecting this gene with primary ciliopathy.